Poczuj swąd. Lönguhlíðarbrenna jako typowa scena literacka - Tirosh, Yoav (Średniowiecze Polskie i Powszechne, 2017)
The scenes of burning down houses along with their inhabitants, present in Icelandic sagas, contribute in a special way to the drama of individual stories. Due to their radical nature, which was also felt by the people of that time, these events remained in people's memory for a long time, gradually becoming an integral part of the literary art practiced there. Scenes of this type proved to be a very good opportunity to highlight not only the intensity of the conflicts described in the sagas and the ruthlessness of the people involved in them. On this occasion, the audience of the sagas could particularly well see the qualities and characteristics (or lack thereof) that they expected from the heroes of the sagas, such as loyalty, honor, and respect for the law. The author refers to the discussion on the role of such scenes in individual stories. The article thus attempts to answer the question of to what extent they were merely a fictional element influencing the shape of the narrative (elimination of individual heroes, the source of conflict, incitement to revenge), and to what extent their literary arrangement referred to authentic cases known to the audience of the sagas. Based on specific examples taken from family sagas (The Saga of Njal) or so-called contemporary sagas (The Saga of Gudmund the Noble), the author leans towards the opinion that the burning scenes were constructed in a way that allowed the audience to believe that the fictional story could have taken place in the past. A key role was played here by the appropriately portrayed attitudes of the people who were burned in these scenes.